Single-atom nanozyme with asymmetric electron distribution for tumor catalytic therapy by disrupting tumor redox and energy metabolism homeostasis - Liu, Yang (2024)
Nanozyme catalytic therapy triggered by tumor-specific endogenous stimuli is an emerging tumor therapy that attracts wide attention. However, the current therapeutic efficacy of nanozyme catalytic therapy is severely limited by the catalytic efficiency of nanozymes and the concentration of endogenous reaction substrates. Herein, a novel and efficient IrN5 single-atom (IrN5 SA) nanozyme is developed with multiple enzyme-like catalytic activities. Due to the synergistic effect of central Ir single-atom and axial N coordination, IrN5 SA exhibits better enzymatic catalytic performance than IrN4 SA. At tumor sites, IrN5 SA can generate a large amount of reactive oxygen species (ROS) through oxidase (OXD)-like and peroxidase (POD)-like catalytic activities. Moreover, IrN5 SA can also generate O2 and hydrogen peroxide (H2 O2 ) through catalase (CAT)-like and nicotinamide adenine dinucleotide (NADH) oxidase (NOX)-like catalytic activities, realizing the efficient nanozyme catalytic therapy in a substrate-cycle manner. Additionally, IrN5 SA can effectively break the intracellular NADH/NAD+ cycle balance by mimicking NOX, and then cooperate with fatty acid synthase cerulenin (Cer) to interfere with the energy metabolism homeostasis of tumor cells. Consequently, the designed IrN5 SA/Cer nanoagent can disrupt redox and metabolic homeostasis in the tumor region through an enzyme-mimicking cascade reaction, effectively overcoming the shortcomings of current nanozyme catalytic therapy.